STUDI EKSPLORASI SISTEM SIARAN TELEVISI BERJARINGAN DI INDONESIA - Primasanti, K.B. (Scriptura, 2009)
Television networking system is not a new theme in broadcasting. For some years, television networking system has been applied in many countries. Nowadays, Indonesia also has a willingness to apply television networking system. It is legalized trough it’s broadcasting law no 32/ 2002. Unfortunately, until two periods of waiting, this regulation has not been implemented yet. Many factors are potential to be the causes of this problem; so it is a must to explore the term of television networking system and the implementation in Indonesia in order to give a mental picture about television networking system. This exploration study has explored the term of television networking system and it’s application in Indonesia by refers to America’s and British’s as earlier country which have implemented television networking system. Trough this exploration, television networking system has been mapped into the definition: the crucial characters it has and the aspects which support it’s growth. Trough the economic politic media perspective, this study has also mapped the strengths and the weaknesses of television networking system in Indonesia. This study conclude that although there must be many factors to be prepared before the implementation of television networking system, it is still possible to implement it in Indonesia trough many alternatives adjusted to our nation condition in the perspective of democtratization.